Future Research Directions for Understanding Neighborhood Contributions to Health Disparities - Osypuk, Theresa L. (2013)
This paper proposes several promising future directions for neighborhood research to address health inequalities. First, there is a need to apply a Geography of Opportunity framework to understand how vast spatial (neighborhood, regional) inequality translates into health inequality. Such a framework highlights inequality that unfolds across an entire region, as well as the continuing significance of race/ethnicity for producing disparities in health and in the social determinants of health. The Geography of Opportunity framework also points to some of the methodological limitations of current neighborhood health studies, given the structure of neighborhood racial inequality in the US for estimating how important neighborhoods are for producing racial health disparities. Second, there is a need to incorporate life course concepts, data, and methods, including to model residential histories, neighborhood temporal change and residential mobility, starting early in life. A life course focus would help inform when in life neighborhoods matter most for health and health inequalities, as well as improve exposure assessment of residential contexts. Third, we must model mechanisms linking neighborhoods and health, including the role of individual and household socioeconomic status (SES). Lastly, we need to more meaningfully integrate social determinants of health, including drawing on policy evaluations that aim to improve neighborhood environments or that aim to expand household neighborhood choice. Doing so would inform how specific modifiable neighborhood exposures stimulated by policy may influence health and health disparities.